IMPLEMENTATION OF E-GOVERNMENT IN THE PROMOTION PROCESS OF CIVIL SERVANTS AT THE HEALTH OFFICE OF BOGOR REGENCY - Iska Hartita, Rita Rahmawati, Rusliandy (Integrative Perspectives of Social and Science Journal, 2026)
This study examines the implementation of e-government in the promotion process of civil servants at the Health Office of Bogor Regency using the Government to Employee (G2E) framework. Employing a descriptive qualitative approach, data were collected through interviews, observation, and documentation. The findings show that the Civil Servant Information System (SIASN) improves administrative efficiency, transparency, and accountability by digitizing procedures. However, implementation remains constrained by uneven system accessibility, limited digital competence, insufficient organizational support, and weak system integration. The study also identifies issues such as digital inequality and operational dependency, indicating a gap between technological adoption and effective governance transformation. Therefore, successful e-government requires alignment between technology, human resources, and institutional capacity.